The Influence of Audit Expertise and Audit Intuition on Fraud Detection with Audit Experience as a Moderator at Kantor Akuntan Publik in Indonesia - Juninetenth Keeply F Sitanggang; M. Irsan Nasution; Renny Maisyarah (Journal of Research in Social Science and Humanities, 2025)
Fraud detection remains a critical challenge for public accounting firms (KAP) in Indonesia due to the increasing complexity of business transactions and fraudulent schemes. This study examines the influence of audit expertise and audit intuition on fraud detection, with audit experience serving as a moderating variable. A quantitative research design was employed using survey data collected from 381 auditors working at public accounting firms across Indonesia. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to test both direct and moderating effects. The results indicate that audit expertise has a positive and significant effect on fraud detection, while audit intuition also significantly enhances auditors’ ability to identify fraudulent activities. Furthermore, audit experience strengthens the relationship between audit expertise and fraud detection, as well as between audit intuition and fraud detection, suggesting that experienced auditors are better able to translate technical skills and intuitive judgment into effective fraud identification. These findings contribute to behavioral auditing literature by integrating cognitive and experiential factors in fraud detection. Practically, the results highlight the importance of developing auditors’ technical competencies, intuitive judgment, and experiential learning to improve audit quality and fraud detection effectiveness in public accounting firms